THE USE OF EFFECTIVE METHODS THROUGH FOLK MUSIC IN EDUCATION (TAMADDUN NURI JURNALI, 2025)
Folk music is an integral part of the cultural heritage of every nation, it reflects the historical, cultural and spiritual life of the people. The process of teaching folk music to students helps not only to develop musical skills, but also to understand their cultural and historical life. This article provides information about effective methods and methods of teaching folk music.